Measuring SDG Contribution Through Sustainability Accounting: A Framework for Emerging Markets - Rumasukun, Mohammad Ridwan (Journal of Sustainability Industrial Engineering and Management System, 2025)
This study aims to develop a comprehensive conceptual framework for measuring corporate contributions to the Sustainable Development Goals (SDGs) in emerging markets through sustainability accounting. Motivated by persistent variation in SDG reporting quality and the continuing disconnect between disclosure and actual sustainability performance, the research seeks to clarify how sustainability accounting can function not only as a reporting mechanism but also as a strategic performance measurement system. Employing a qualitative, literature-based methodology, the study synthesizes findings from recent empirical and theoretical research across sustainability accounting, ESG disclosure, SDG alignment, governance studies, and institutional analysis. The results reveal that sustainability accounting in emerging markets is expanding but remains uneven, often characterized by symbolic disclosure practices and fragmented indicator systems. Strong governance structures, robust internal management controls, and supportive institutional environments emerge as critical enablers of reliable, SDG-aligned sustainability accounting. The study further identifies a mediating relationship whereby sustainability accounting generates structured ESG information that supports SDG performance when indicators are explicitly linked to SDG targets and embedded within strategic decision-making processes. The main contribution of the research is the formulation of an integrative framework that positions sustainability accounting as a multidimensional tool for SDG measurement, emphasizing indicator alignment, governance quality, management integration, and institutional adaptability. These findings offer theoretical insights into the evolving nature of sustainability accounting and practical guidance for firms and policymakers seeking to strengthen SDG reporting and accelerate sustainable development outcomes in emerging economies.